GENERAL METHODOLOGY OF TEACHING - Embergenova N. (Journal Park Publishing, 2023)
The general methodology - some general philosophical approach, the general way of knowledge accepted by the researcher. The general methodology formulates some people most the general principles which - osoznanno or neosoznanno - are applied in researches. So, for social psychology the certain understanding of a question on a parity of a society and the person, human nature is necessary.
Keywords: general methodology, teaching methods, English.